HUBUNGAN POWER OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN SABIT SISWA SMA MUHAMMADIYAH BANGKINANG - Edwar, Een Rosalina; Wijayanti, Niputu Nita; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT : This study was conducted to determine whether there is a relationship muscle power with the speed of a crescent kick high school students muhammadiyah bangkinang, so that at the time of the crescent kick can be done with maximum speed. The shape of this research is a correlation study, the population in this study were high school students muhammadiyah bangkinang who follow extracurricular, the sample in this study were high school students muhammadiyah bangkinang and amounted to 15 people. Sampling technique that overall population (total sampling). The instruments used in this research is the limb muscle power tests, which aims to measure limb muscle power then test speed crescent kick that aims to measure the speed of a crescent kick. After that, the data is processed with statistics, to test the normality of the test at a significant level 0,05Î± lilifors. The hypothesis is alleged there is a significant relationship between the muscle power with the speed of a crescent kick high school students muhammadiyah bangkinang. Based on test analysis lilifors produce Lhitung (x) of 0,1255 and 0,220 Ltabel, Lhitung (y) for 0,0664 and Ltabel 0,220 means Lhitung <Ltabel, the sample comes from a population of normal distribution. Then from the calculation of the product moment correlation between muscle power with the speed of a crescent kick acquired rhitung 0,08621 and 0,532 rtabel means rhitung> rtabel consequently Ha Ho is accepted and rejected.Thus there is a significant relationship between the muscle power with the speed of a crescent kick high school students muhammadiyah bangkinangKeywords: Muscle Power , Speed Of A Crescent Kick